Asymptotic BLSCP models in uncertain and asymmetric environments—Take the charging station location problem - Muren; Yihao Li; Zhiqiang Xu (PLoS ONE, 2025)
The rapid development of the field of vehicles exposes many problems of charging station, the most common is the uncertainty and asymmetry of its task volume, so the flexibility of location and scale design is crucial. This paper proposes the asymptotic BLSCP model, suitable for uncertain and asymmetric environments, which balances facility workload and minimizes cost through the forward or backward asymptotic methods of candidate center locations and flexible allocation of jurisdictions. Additionally, the findings suggest these methods possess considerable potential for application and generalization.